Recurrent Kimura’s disease successfully treated with steroids and cetirizine - Kuruvilla, Shalini; Kuruvilla, Rojan; Bhasi, Remesh; M, Lilly (International Surgery Journal, 2016)
Kimura’s disease is a rare cause of a neck mass. A case of Kimura’s disease presenting as a recurrent neck mass following previous excision is presented. Preoperative diagnosis may be possible if the eosinophilia is noted and a serum IGE is estimated. Surgery is the primary modality of treatment. Diagnosis is confirmed by histology. Steroids and Cetirizine are effective in the management of recurrences.